2014
DOI: 10.1055/s-0034-1396005
|View full text |Cite
|
Sign up to set email alerts
|

Hemispatial Neglect: Clinic, Pathogenesis, and Treatment

Abstract: Hemispatial neglect is characterized by a failure of awareness on the side of space and body opposite the site of injury, has been extensively studied for its theoretical interest in revealing brain mechanisms of awareness and attention. More recently, it has become apparent that hemispatial neglect reflects not only damage of specific anatomical regions, but also the large-scale dysfunction of networks of brain regions specialized in attention, motor, and multimodal sensory processing. Finally, although previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 57 publications
1
41
0
4
Order By: Relevance
“…The vast majority of studies conducted with stroke survivors have focused on anosognosia of hemiparesis , which is estimated to affect ~30% of stroke survivors (Kortte & Hillis, 2009; Nurmi Laihosalo & Jehkonen, 2014). However, it is well recognized clinically that stroke survivors with neglect often have limited insight to their neglect and how neglect affects their ability to perform daily activities (Corbetta, 2014; Prigatano, 2014). Hence, this study uniquely focuses on anosognosia of neglect .…”
mentioning
confidence: 99%
“…The vast majority of studies conducted with stroke survivors have focused on anosognosia of hemiparesis , which is estimated to affect ~30% of stroke survivors (Kortte & Hillis, 2009; Nurmi Laihosalo & Jehkonen, 2014). However, it is well recognized clinically that stroke survivors with neglect often have limited insight to their neglect and how neglect affects their ability to perform daily activities (Corbetta, 2014; Prigatano, 2014). Hence, this study uniquely focuses on anosognosia of neglect .…”
mentioning
confidence: 99%
“…Hence, fluctuations in performance can additionally be measured during the task, but also in the course of rehabilitation, because of the consistency across assessments. Previous studies with VSN patients have reported inconsistency in performance throughout the day (Corbetta, ) and during the period of recovery (Jehkonen, Laihosalo, Koivisto, Dastidar, & Ahonen, ). The simulated driving task could serve as dynamic task to assess mild VSN and to further explore fluctuations in performance among VSN patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the nature of the task (static versus dynamic) can cause differences in performance. Furthermore, the heterogeneity of VSN also extends to modality (i.e., visual, auditory or tactile), frame of reference (i.e., egocentric or allocentric), or region of space (i.e., peripersonal or extrapersonal) (Corbetta, 2014;Rode, Pagliari, Huchon, Rossetti, & Pisella, 2016;Van der Stoep et al, 2013). With the simulated driving task, we only measured lateralized visuo-spatial inattention.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to one side of the brain, typically the right temporoparietal junction (TPJ), causes a loss of awareness of everything to the opposite side of space (Vallar and Perani, 1986;Corbetta, 2014). Yet, information from the neglected side is still processed to some degree (Marshall and Halligan, 1988), and the visual system is still active to the highest levels of processing (Rees et al, 2000;Vuilleumier et al, 2002).…”
Section: The Adaptive Value Of An Attention Schema: Social Cognitionmentioning
confidence: 99%
“…Yet, information from the neglected side is still processed to some degree (Marshall and Halligan, 1988), and the visual system is still active to the highest levels of processing (Rees et al, 2000;Vuilleumier et al, 2002). Neglect appears to be caused by the disruption of brain networks involved in attention and awareness that pass through the TPJ (Corbetta, 2014;Igelström and Graziano, 2017).…”
Section: The Adaptive Value Of An Attention Schema: Social Cognitionmentioning
confidence: 99%